2019
DOI: 10.1051/e3sconf/201912808003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental analysis of the air stream generated by square ceiling diffusers

Abstract: Ceiling diffusers are one of the most important elements of ventilation and air-conditioning installations. They have a significant impact on the speed and temperature distribution of air. The basic task of these devices is to provide the required air stream while maintaining its appropriate parameters in the occupied zone and low noise levels in the room. Square ceiling diffusers are designed for use in low- and medium-pressure ventilation systems. The diffusers allow obtaining 1, 2, 3 or 4-way air supply. Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The supply airflow of each terminal is not independent within the room, but rather has a mutual influence due to the air movement. The airflow distribution on the outlet cross-section of the diffuser directly determines the mixing effect of neighboring airflows, which has an impact on the indoor temperature distribution [30,31]. The current methods do not fully consider the mutual influence among diffusers and their co-impacts on indoor temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The supply airflow of each terminal is not independent within the room, but rather has a mutual influence due to the air movement. The airflow distribution on the outlet cross-section of the diffuser directly determines the mixing effect of neighboring airflows, which has an impact on the indoor temperature distribution [30,31]. The current methods do not fully consider the mutual influence among diffusers and their co-impacts on indoor temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was concluded from the study that the multi-cone diffuser was a better overall performer among the two. Jaszczur et.al 10) performed a study of the air stream generated by the square ceiling diffusers. An experimental and numerical study of a single square ceiling diffuser was performed.…”
Section: Introductionmentioning
confidence: 99%
“…The way air is distributed into the room is closely related to the construction of the air diffuser. A number of research studies on air distribution from diffusers can be found in the literature [7,8], including those using a numerical calculation [9,10]. Yao and Lin [11] analyzed the effect of air terminal types on the performance of stratum ventilation with four types of air terminals devices using experimental and numerical methods.…”
Section: Introductionmentioning
confidence: 99%